Reaktualisasi Behavioristic Approach Dalam Mengatasi Learning Difficulty - Nofita Rahmawati, Roro Kurnia (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2022)
The diverse characteristics of students are a separate problem for educators in choosing and using the right approach. Learning difficulties experienced by students are also often difficult problems to solve, so teachers are required to find effective solutions in the context of classroom learning. The method used in this research is qualitative with the type of library research. The results of this study show that learning using a behavioristic approach is highly recommended for an educator because this approach tends to make learning more meaningful. Learning difficulties experienced by students can be overcome more when a teacher uses a behavioristic approach with operant conditioning techniques because this approach is oriented towards changes in behavior that appear in the environment through the learning process. Constructive changes in student behavior can be achieved so that the difficulties found can be overcome